Hybrid Type Rigid Plastic Finite Element Analysis for Bearing Capacity Characteristics of Surface Uniform Loading - Kobayashi, Shun-ichi (SOILS AND FOUNDATIONS, 2005)
In the geotechnical engineering design, rigid plastic analysis is usually used to estimate a factor of safety or an ultimate capacity. Although based on a simple assumption of rigid-plastic material behaviour, limit analysis has a rigorous theoretical background called limit theorems. The implementation of limit analysis to finite element method is recognised as rigid-plastic finite element method. The author recently proposed a new formulation of hybrid type rigid-plastic finite element method based on the interior point method, named primal-dual rigid-plastic finite element method (PDRPFEM). In this paper, characteristics of primal-dual rigid-plastic finite element method are illustrated in contrast to the ordinary rigid-plastic finite element method based on the upper bound theorem. Advantages of the primal-dual rigid-plastic finite element method in the numerical calculations are also explained. In addition to this, as a real rigid-plastic boundary value problem, bearing capacity problems of surface uniform loading on weightless Tresca material (c, φ = 0) are solved by the primal-dual rigid-plastic finite element method. Numerical solutions are compared to the analytical solutions to investigate numerical accuracies of the primal-dual rigid-plastic finite element method.